Nitrogen Fertilization Guidelines for Potato Production in Florida - Lincoln Zotarelli; Tara Wade; Gary England; Christian Christensen (EDIS)
This new 11-page publication focuses on the nitrogen (N) fertilizer best management practices (BMP) for potato crop in Florida. The aim is to provide management strategies that comply with statewide BMP guidelines to maximize yield and economic return while minimizing N losses to the environment. Written by Lincoln Zotarelli, Tara Wade, Gary K. England, and Christian T. Christensen and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1429